2010
DOI: 10.1007/s00417-010-1384-z
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of diabetic retinopathy by engrafted human adipose-derived mesenchymal stem cells in streptozotocin diabetic rats

Abstract: Taken together, the results of the current study suggest that AMSCs may improve the integrity of the BRB in diabetic rats by differentiation into photoreceptor and glial-like cells in the retina and by reducing the blood glucose levels. Furthermore, the data presented herein provide evidence that AMSCs may serve as a promising therapeutic approach for diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 25 publications
1
65
1
3
Order By: Relevance
“…Although most cells remained in spleen and thymus, a relatively high percentage of ASC were found in injured region. Moreover, Yang et al had found that engrafted ASC homed to retina and differentiated into photoreceptorlike cells and astrocyte-like cells induced by diabetic retinopathy, and ameliorated the integrity of the bloodretinal barrier [31]. Based on the above findings, we considered that ASC could home to the damaged islets to play their roles.…”
Section: Discussionmentioning
confidence: 80%
“…Although most cells remained in spleen and thymus, a relatively high percentage of ASC were found in injured region. Moreover, Yang et al had found that engrafted ASC homed to retina and differentiated into photoreceptorlike cells and astrocyte-like cells induced by diabetic retinopathy, and ameliorated the integrity of the bloodretinal barrier [31]. Based on the above findings, we considered that ASC could home to the damaged islets to play their roles.…”
Section: Discussionmentioning
confidence: 80%
“…When (17) reported that co-transplantation of adipose tissuederived insulin-secreting MSCs and hematopoietic stem cells is beneficial in reducing exogenous insulin requirement in patients with insulin-dependent diabetes mellitus. It has also been demonstrated that transplantation of ADMSCs attenuates diabetic bladder dysfunction and diabetic retinopathy in a diabetic rat model (18,19). Based on these previous findings, we therefore raised the hypothesis that cytotherapy using autologous ADMSC transplantation is beneficial in alleviating diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 81%
“…Another study has shown that intravenous injection of human adipose-derived MSCs into rats having established DR has led to improved blood retinal barrier integrity [102]; some donor cells differentiated into photoreceptor or astrocyte-like cells inside the retina of these rats [102]. A single intravitreal injection of placental-derived MSCs into diabetic rats has also resulted in a significant decrease in retinal cell apoptosis, such effect being related to increased intravitreal concentration of several neuroprotective growth factors [103].…”
Section: Msc-related Therapy For Diabetic Retinopathymentioning
confidence: 99%